“Se stai per presentare la tua offerta allʼaltare…” (Mt 5,23-24). La testimonianza di unʼiscrizione palestinese - Piccirillo, M.; Bottini, G.C. (Liber Annuus, 2006)
Abstract The rareness of the epigraphical witness contrasts the frequency with which Mt 5:23-24 was quoted and commented upon by the ancient christian writers. Hereby we publish an inscription of Palestinian origin that in itʼs partial form, casually came to our knowledge. The carving found on a tabula ansata, detached from its original context, was a part of the Churchʼs original mosaic pavement. The first words allowed us to identify the quotation from the Sermon on the Mount according to the gospel of Saint Matthew 5:23-24, therefore with good probability; we can complete the text that in the fourth line resumes the generic dedication to the Churchʼs benefactors. The rareness of the epigraphical witness contrasts with the frequency with which Mt 5:23-24 was quoted and commented upon by the ancient christian writers.